1971
DOI: 10.1021/i160037a002
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Glucose Metabolism in Man

Abstract: The development of a three-compartment model for glucose metabolism in man is discussed. A nonlinear regression method was used to determine the parameters of the model by simultaneously fitting typical blood glucose and breath COs specific activity data obtained after intravenous administration of C14-tagged glucose. The three-compartment model is compared with a two-compartment model on the basis of ability to fit the data, confidence limits on the best parameter values, strength of parameter correlation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Carbohydrate stores within the body were insignificant, and after even short periods of starvation body glucose needs are met by an increased liver production of glucose from protein precursors. Using an isotopic tracer technique (Spencer, Long & Kinney, 1971), it was established that in the late recovery phase following severe injury, and in sepsis, both glucose oxidation and gluconeogenesis were increased (Long, Spencer, Kinney & Geiger, 1971 ; Gump, Long, Killian & Kinney, 1974) and that gluconeogenesis could not be suppressed by intravenous infusion of glucose (Long, Kinney & Geiger, 1976). This suggested that after injury the normal neurohumoral regulation of gluconeogenesis with muscle and liver had ceased to be effective.…”
Section: Symposium Proceedings I978mentioning
confidence: 99%
“…Carbohydrate stores within the body were insignificant, and after even short periods of starvation body glucose needs are met by an increased liver production of glucose from protein precursors. Using an isotopic tracer technique (Spencer, Long & Kinney, 1971), it was established that in the late recovery phase following severe injury, and in sepsis, both glucose oxidation and gluconeogenesis were increased (Long, Spencer, Kinney & Geiger, 1971 ; Gump, Long, Killian & Kinney, 1974) and that gluconeogenesis could not be suppressed by intravenous infusion of glucose (Long, Kinney & Geiger, 1976). This suggested that after injury the normal neurohumoral regulation of gluconeogenesis with muscle and liver had ceased to be effective.…”
Section: Symposium Proceedings I978mentioning
confidence: 99%
“…Tracer studies with 14C-glucose have been employed with a mathematical model developed by Dr Jordan Spencer to relate blood and breath specific activities and the rate of CO2 production to the rate of glucose turnover and oxidation in surgical patients (Spencer, Long and Kinney, 1970). To date, 35 glucose runs have been made, including 14 volunteers (Long, Spencer, Kinney, and Geiger, 1970a) or patients undergoing elective surgery.…”
Section: Intermediary Metabolism After Injurymentioning
confidence: 99%